Correlation between class 1 integron of Escherichia coli and multidrug resistance in lower respiratory tract infection - Yu Wang; Bingbing Kong; Wenping Yang; Xin Zhao (Journal of Infection in Developing Countries)
Introduction: Class 1 integrons are mobile genetic elements considered to be responsible for the transfer of multidrug resistance. This study aimed to investigate the distribution of type 1 integrons in multidrug-resistantEscherichiacolifrom hospital-acquired lower respiratory tract infections.